Remote Real-Time Ultrasound Supervision via Commercially Available and Low-Cost Tele-Ultrasound: a Mixed Methods Study of the Practical Feasibility and Users’ Acceptability in an Emergency Department - Jensen, Stig Holm (J Digit Imaging, 2018)
Minor emergency departments (ED) struggle to access sufficient expertise to supervise learners of lung and cardiac point-of-care ultrasound (POCUS). Using tele-ultrasound (tele-US) for remote supervision may remedy this situation. We aimed to evaluate the feasibility of real-time supervision via tele-US when applied to an everyday ED clinic. We conducted a mixed methods study that assessed practical feasibility, determined performance, and explored users’ acceptability of supervision via tele-US. Technical performance was assessed quantitatively by the ratio in mean gray value between images on site and as received by the supervisor, and by after-compression frame rate. Qualitatively, 12 exploratory semi-structured interviews were conducted with exposed junior doctors and supervisors. Remote supervision via tele-US was performed with 10 junior doctors scanning 45 included patients. During performance assessment, neither alternating internet connection nor software significantly changed the mean gray value ratio. The lowest median frame rate of 4.6 (interquartile range [IQR]: 3.1–5.0) was found by using a 4G internet connection; the highest of 28.5 (IQR: 28.5–29.0) was found with alternative computer and local area network internet connection. In interviews, supervisors stressed the importance of preserving frame rate, and junior doctors emphasized a need for shared ultrasound terminology. In the qualitative analysis, setup mobility, accessibility, and time consumption were emphasized as being of key importance for future clinical implementations. Remote supervision via a commercially available and low-cost tele-US setup is operational for both junior doctors and supervisors when applied to lung and cardiac POCUS scans of hospitalized patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10278-018-0157-9) contains supplementary material, which is available to authorized users.